2004
DOI: 10.1177/096739110401200101
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Polymerization-Filled Kevlar Pulp/Polyethylene Composites

Abstract: Polymerization-filled composites (PFC) and melt-blended composites (MBC) of Kevlar pulp/high density polyethylene composites were prepared to compare their mechanical properties. It was found that break strains of PFC composites were by far higher than MBC composites for a similar fiber concentration. Tensile data were then used to compare several models of short fiber polymer composites. Of all the models tested, it was found that Berlin's approach in combination with Rosen's model for critical aspect ratio g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Several works have been done to determine the effect of short fibers on the properties of polymer composites [41][42][43][44][45][46][47][48][49][50][51][52] . Here, we investigated the elastic modulus of short fiber composites and comparison is made with well known models for randomly oriented short fiber composites 53 , such as Halpin-Tsai for 2D and 3D randomly oriented short fiber composites 51,52 , numerical integration of angular dependence of the modulus of 2D randomly oriented short fiber composites based on the model of Tsai-Hill [42][43] , and the model of Berlin et al 46 for Young's modulus of 3D randomly oriented short fiber composites including the fiber critical aspect ratio determined by three methods [47][48][49][50] . Of all the models tested, it was found that Berlin's approach for 3D randomly oriented short fiber composites in combination with the critical fiber aspect ratio given by Rosen's model produce reasonable prediction for PFC composites using: where E comp is the modulus of 3D randomly oriented short fiber composite, E fiber is the fiber modulus, E m is the matrix modulus, ϕ fiber is fiber volume fraction of unfoamed composites, l is fiber length, l c is the critical fiber length, l max is the maximum fiber For our composites foams, the Kevlar is dispersed in the solid phases of the foam.…”
Section: Modulus Relationship Between Composite Foams and Polymer Matrixmentioning
confidence: 99%
“…Several works have been done to determine the effect of short fibers on the properties of polymer composites [41][42][43][44][45][46][47][48][49][50][51][52] . Here, we investigated the elastic modulus of short fiber composites and comparison is made with well known models for randomly oriented short fiber composites 53 , such as Halpin-Tsai for 2D and 3D randomly oriented short fiber composites 51,52 , numerical integration of angular dependence of the modulus of 2D randomly oriented short fiber composites based on the model of Tsai-Hill [42][43] , and the model of Berlin et al 46 for Young's modulus of 3D randomly oriented short fiber composites including the fiber critical aspect ratio determined by three methods [47][48][49][50] . Of all the models tested, it was found that Berlin's approach for 3D randomly oriented short fiber composites in combination with the critical fiber aspect ratio given by Rosen's model produce reasonable prediction for PFC composites using: where E comp is the modulus of 3D randomly oriented short fiber composite, E fiber is the fiber modulus, E m is the matrix modulus, ϕ fiber is fiber volume fraction of unfoamed composites, l is fiber length, l c is the critical fiber length, l max is the maximum fiber For our composites foams, the Kevlar is dispersed in the solid phases of the foam.…”
Section: Modulus Relationship Between Composite Foams and Polymer Matrixmentioning
confidence: 99%
“…In a previous study 14 , the fiber critical aspect ratio (l c /d) was determined by three methods. In method I, the critical aspect ratio was obtained based on fiber strength (σ f ) and interfacial shear strength (τ) as l c /d = σ f /(2τ).…”
Section: Randomly Oriented Short Fiber Compositesmentioning
confidence: 99%
“…Kevlar pulp was kindly provided by Dupont Canada (Toronto, Canada). Polymerization-filled Kevlar pulp was prepared in a batch reactor at 60°C as reports elsewhere 14 . Because of the limited amount available, no systematical determination of the polyethylene molecular weight and molecular weight distribution in polymerization-filled Kevlar pulp could be achieved.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 2 more Smart Citations